Nuclear translocation of UDCA by the glucocorticoid receptor is required to reduce TGF-beta 1-induced apoptosis in rat hepatocytes - Sola, S (2015)
Ursodeoxycholic acid (UDCA) inhibits classical mitochondrial pathways of apoptosis by either directly stabiliz* mitochondrial membranes or modulating specific upstream targets. Furthermore, UDCA regulates apoptosis-related genes from transforming growth f